Developing Differentiated Content of PAI Based on Divergent Thinking: A Define-Stage of Khalifa Abu Bakr as-Siddiq at SDN 02 Pariangan - Gusrina Fadhila; Syahrur Ramli; Nadia Zakia (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2026)
This research aims to analyze the necessity of developing differentiated Islamic Cultural History (SKI) content during the define stage to stimulate the divergent thinking skills of elementary school students. The primary problem driving this study is the prevalence of rigid rote-learning patterns that stifle students' creativity and original ideation when attempting to understand historical dynamics. Specifically, initial diagnostic assessments at SDN 02 Pariangan revealed low performance in fluency, flexibility, originality, and elaboration indicators, as students struggled to engage with the complex leadership and strategic policies of Khalifa Abu Bakr as-Siddiq. This study utilizes a Research and Development (R&D) approach, adopting the 4D development model which encompasses the define, design, develop, and disseminate phases. The methodology is specifically focused on the Define stage, incorporating front-end analysis, learner analysis, task analysis, concept analysis, and the specification of learning objectives for eighteen sixth-grade students at SDN 02 Pariangan. Findings indicate that efforts to enhance divergent thinking are realized by integrating problematic historical narratives as a cognitive stimulus to trigger diverse, open-ended, and non-linear exploration of ideas. The form of content differentiation is implemented by presenting the biography and policies of Abu Bakr through various modalities—visual, auditory, and kinesthetic—while adjusting difficulty levels to align with each student's unique learning profile. The urgency of this research underscores the necessity of an inclusive and responsive Merdeka Curriculum to equip the younger generation with analytical sharpness and intellectual courage to navigate complex global challenges.